Walk to stay healthy and creative - Abdul Razak, Mohd Abbas; Mustapha, Maziah (Department of Communication, Kulliyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), IIUM, 2024)
From time immemorial, human beings have been walking. Unlike trees, animals and humans are given the ability by God the Almighty to move around with their legs. In the case of human beings, they walk for a wide range of reasons to fulfil their human needs. In the olden days, long before the advancement in the field of medicine, people walked a lot and never thought it was a form of exercise to stay healthy. As modernisation ushered in, it provided comforts to our lives. Modern means of moving around pampered us too much, to the extent that one section of humanity became indolent and never wanted to walk even to accomplish simple tasks like: climbing a staircase or walking to a nearby cafe or a grocery market. The Apps for everything on the smartphone give them the feeling that the whole world is in service to them. Since everything can be delivered to their doorways, they feel they don’t have to move around and feel exhausted and sweaty. Quite the opposite of the indolent ones mentioned above, even with modern comforts, the other segment of humanity still preferred to walk short distances to accomplish simple tasks in daily life. For them, walking re-energizes their bodies, and meeting neighbours and other people brings joy to their hearts. Even today, in many dry regions of the world, people walk many miles in search of food and water. In such an environment, it is a necessity to walk and find nourishment for their bodies. Without doing so, the risk of dying is very high. Contrastively, in the affluent countries of the world, people need to walk as an exercise to burn the excessive calories in their bodies. Failure to do so will result in health issues that can be fatal.